CCAAT/enhancer binding protein alpha is sufficient to initiate the 3T3-L1 adipocyte differentiation program. - Lin, F T (1994)
Previous studies showed that CCAAT/enhancer binding protein alpha (C/EBP alpha) is required for differentiation of 3T3-L1 preadipocytes induced by exogenous hormonal agents. It was not possible to ascertain, however, whether C/EBP alpha alone is sufficient to induce differentiation because its antimitogenic activity precluded propagating 3T3-L1 cell lines that constitutively express C/EBP alpha at high levels. This problem was circumvented by using 3T3-L1 preadipocytes stably transfected with an isopropyl beta-D-thiogalactoside (IPTG)-inducible p42 C/EBP alpha expression vector system. IPTG-induced expression of the 42-kDa isoform of C/EBP alpha in preadipocytes caused expression of several endogenous adipocyte-specific genes (genes encoding the 422 adipose P2 protein, glucose transporter 4, and C/EBP alpha) and the accumulation of cytoplasmic triglyceride. Thus, C/EBP alpha is not only necessary but also is sufficient to trigger differentiation of growth-arrested 3T3-L1 preadipocytes without use of exogenous hormonal agents.